1996
DOI: 10.1021/ma9602379
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Models for Carbocationic Polymerization:  Influence of Chain Length on Carbocation Reactivities

Abstract: The kinetics of the reactions of the carbocations CH3[C(CH3)2CH2] n C+Ph2 (1a +−1d +, n = 0, 1, 2, 34) with allyltrimethylsilane (4) and dimethylphenylsilane (5) have been investigated. It is found that the carbocation 1a + (n = 0) is 102 times more reactive than the more highly substituted analogues 1b +−1d +, which hardly differ in their electrophilic reactivity. We, therefore, conclude that the (CH3)3CCH2 and (CH3)3CCH2C(CH3)2CH2 groups are suitable to mimic the polyisobutylene chain in a growing carbocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…In the case of EBP and EBiB the PMMA • is more stable due to the back strain effect, in which the release of steric strain from the dormant PMMA-Br species as it undergoes transformation from a sp 3 hybridized to sp 2 hybridized configuration through activation makes the formation of the radical more enthalpically valuable. 47,48 Taken altogether, this data concludes that in the case of acrylates, all three initiators result in narrow molecular weight distributions although clearly MBPA is less ideal due to much slower polymerization rates. On the contrary, in the case of methacrylates only MBPA can facilitate a well-controlled polymerization delivering polymers of low dispersity.…”
Section: Resultsmentioning
confidence: 72%
“…In the case of EBP and EBiB the PMMA • is more stable due to the back strain effect, in which the release of steric strain from the dormant PMMA-Br species as it undergoes transformation from a sp 3 hybridized to sp 2 hybridized configuration through activation makes the formation of the radical more enthalpically valuable. 47,48 Taken altogether, this data concludes that in the case of acrylates, all three initiators result in narrow molecular weight distributions although clearly MBPA is less ideal due to much slower polymerization rates. On the contrary, in the case of methacrylates only MBPA can facilitate a well-controlled polymerization delivering polymers of low dispersity.…”
Section: Resultsmentioning
confidence: 72%
“…Similar effects were previously reported on the solvolysis of alkyl halides and ionization of alkyl halides to sp 2 -hybridized carbocations. 31,32 The presence of a penultimate unit effect was reported earlier in propagation studies. At 60°C, the rate constant of addition of the H-MMA • radical (i.e., methyl isobutyryl radical) to MMA was 3.9 times higher than that of the H-MMA-MMA • dimeric radical and 17 times higher than a value of k p from PLP measurements.…”
mentioning
confidence: 57%
“…Mayr et al reported on models for carbocationic polymerizations employing similar end group functionalized polyisobutylenes. [14] Accordingly, we have checked the synthesis of a block copolymer by cationic initiation with the bis(4-methoxyphenyl)methylium-head group functionalized PIBVE on silica. The use of carbenium head group functionalized polymers for block copolymer synthesis, which are obtained by a hydride transfer reaction, has not yet been reported in the literature.…”
Section: Resultsmentioning
confidence: 99%